Interpretation of the Concept of Rajā’ in QS. Al-Kahfi: 110 from the Perspective of Tafsir Nuzūlī ‘Abdurrahman Habannakah Al-Maidāni - Jaenal Habin (Rumah Moderasi Beragama of UIN Siber Syekh Nurjati Cirebon, 2026)
Purpose ̶ This study aims to revitalize the nuzūlī approach to Qur'anic exegesis by positioning the Qur'an as the central framework of Prophet Muhammad's mission while exploring Habannakah's perspective on the meaning of Qur'an 18:110 within the framework of tadabbur. Design/methods/approach ̶ Using a descriptive-analytical method. Findings ̶ This article finds two main axes. First, Habannakah's interpretation of QS. Al-Kahfi: 110 is based on three main points, namely: Muhammad's humanity, the legitimacy of his prophetic and apostolic status as well as the authenticity of divine revelation, and the warning that worldly life is only a field of trial (al-ibtila'). The first two points are closely related to the theological dimension, while the third point is in line with the Sufi doctrine that dialectically places rajā’ with khauf (fear). Second, from the perspective of the chronological arrangement of the Qur'an, Habannakah's nuzūlī interpretation only covers 87 surahs, consisting of 86 Makkiyyah groups and the rest Madaniyyah. This situation was due to his age when he wrote his interpretation. Conclusion ̶ However, this study notes a limitation, namely the fact that the historical sources used by Habannakah in compiling his chronology have not been identified with certainty. Research Implication ̶ Thus, this gap still opens up opportunities for future researchers to create continuous studies.